Iron-phthalocyanine molecular junction with high spin filter efficiency and negative differential resistance - Huang, Jing (2013)
We investigate the spin transport properties of iron-phthalocyanine (FePc) molecule sandwiched between two N-doped graphene nanoribbons (GNRs) based on the density functional theory and nonequilibrium Green's function methods. Our calculated results clearly reveal that the FePc molecular junction has high spin-filter efficiency as well as negative differential resistance (NDR). The zero-bias conductance through FePc molecule is dominated by the spin-down electrons, and the observed NDR originates from the bias-dependent effective coupling between the FePc molecular orbitals and the narrow density of states of electrodes. The remarkable high spin-filter efficiency and NDR are robust regardless of the edge shape and the width of GNRs, and the N-doping site in GNRs. These predictions indicate that FePc junction holds great promise in molecular electronics and spintronics applications.